UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE DI KELAS XB SMA KATOLIK SANTO BONAVENTURA MADIUN - Patalas, Natalis Nero; Ariyanti, Gregoria (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
The goals of the research are to improve students’ ability in oral and written mathematic comunication by applying cooperative learning model of type think-pair-share in the class X-B of Santo Bonaventura Senior High School of Madiun. It is a class action research with two cycles; each of which has four steps namely, planning, action, observation, and reflection. The instrument of the research is observation sheets used to observe students’ oral mathematic communication ability and written mathematic communication ability using test sheets. The result of the data analysis shows (1) the average score of learning and teaching activity is 2,64 (good) in the first cycle and 3,47 in the second cycle (very good), (2) the average score of students’ oral mathematic communication ability is 2,19 (fair) in the first cycle, and 2,87 (good) in the second cycle, (3) the class average score is 63,30 in the first cycle and 69,87 in the second cycle. The persentage of students’ passing score is 56,52% in the first cycle and 68,18% in the second cycle. Based on the findings of the research, it can be concluded that the application of cooperative learning model of type think-pair-share can improve students’ oral mathematic communication ability but their written mathematic communication ability is not optimal.   Keyword: Mathematical Communication, Cooperative Learning, Think Pair Share